Estimating edible fruit biomass production in the savanna woodlands of KwaZulu-Natal, South Africa. Issue 1 (2nd January 2022) - Akweni, Arindo Lukawu; Sibanda, Sifiso; Zharare, Godfrey Elijah; Zimudzi, Clemence
ABSTRACT: Edible fruits are an important source of food and income in rural areas. The savanna woodlands of South Africa are endowed with a high density of fruit tree species whose production potential has never been investigated. We evaluated this potential for two species ( Strychnos madagascariensis and S. spinosa ) in the central portions of the Umhlabuyalingana Municipality (cpUM). Tree inventories were conducted in eight 0.25-ha square plots following an East-West distance gradient. The diameter at breast height (DBH) of each tree was measured, allowing the estimation of fruit biomass through the use of existing fruit-based allometric equations. The ESRI Calculate Geometry tool of ArcGIS was used to calculate the total surface of the study area, which served to obtain its global fruit biomass production. The productivity of the cpUM was on average 935 ± 532 kg ha −1 and 1211 ± 971 kg ha −1 of fresh fruit biomass, respectively for S. madagascariensis and S. spinosa . For the considered study area, this represented a total production potential of 13, 192 ± 7, 502 tons (t) and 17, 084 ± 13, 695 t of fresh fruit biomass for S. madagascariensis and S. spinosa, respectively. This potential can support commercial harvest ventures of the fruits from the wild.